Dampak Program “Bidan Sahabat” Terhadap Peningkatan Penggunaan Layanan Kesehatan Reproduksi Di Komunitas Marginal - Ula, Zumrotul; Atika, Zummatul (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Access to and utilization of reproductive health services in marginalized communities remains low due to economic, social, and cultural limitations. The Bidan Sahabat program is a health service innovation that aims to bring midwifery services closer to marginalized communities through a persuasive, community-based approach. This study aims to determine the impact of the Bidan Sahabat program on increasing the utilization of reproductive health services in marginalized communities. This study used a quantitative design with a pretest-posttest quasi-experimental approach without a control group. The sample consisted of 60 women of childbearing age living in marginalized communities and was selected using a purposive sampling technique. Data were collected through a questionnaire on reproductive health service utilization and analyzed using a paired t-test. The results showed a significant increase in the utilization of reproductive health services after the implementation of the Bidan Sahabat program with a p-value <0.05. The conclusion of this study indicates that the Bidan Sahabat program has a positive impact on increasing the utilization of reproductive health services in marginalized communities.